8 - Strengthening Rural-Urban Interactions as a Contemporary Paradigm to Sustainable Development in Africa: The Case of Meme Division, South-west Region, Cameroon - Ayuk-Nkem, Agbortoko (Africa Development, 2021)
The world’s population is increasing by around 85 million every year – the equivalent of another Egypt or Mexico, and by 2025 most of the growth is expected to be within urban areas of developing nations. This implies a continuous supply and dependence on raw materials and other infrastructural developments. This study therefore seeks to examine the flow of people, finance through remittances as well as the flow of goods and services between rural and urban settlements in developing nations using the Meme Division of the South-West Region of Cameroon as a case study. The problem of most development theory and practice based on the dichotomy between rural and urban settlements is reflected through the division of policies along spatial and sectoral lines, with urban planners concentrating on urban nodes with less attention to the rural nodes. This has widened the development gap between rural and urban centres, thus accelerating rural-urban migration and a consequent increase in the rate of urban poverty and urban primacy in most developing countries. As its main objective, the study sets out to investigate the relationship between small and intermediate urban centres and their surrounding regions, with particular attention to spatial and sectoral linkages which constitute the basic tenets for a win-win development situation. To attain the objectives, both primary and secondary sources of data were utilized. The secondary sources constituted internet sources and available materials on rural-urban linkages while the primary data was principally from direct interviews and the administration of questionnaires. A systematic sampling technique was used to generate information from the sampled population and the Rank Size Rule was used to analyse the collected data to categorise areas of high linkages and their levels of development. The findings revealed that encouraging rural-urban linkages will constitute a contemporary approach in solving urban problems of increasing slums and urban poverty while reducing rural exodus. From the findings, it was recommended that planning should be done on a regional basis rather than dividing settlements into urban and rural as well as developing transport routes to ease communications between the two areas. The study concludes that regional development as a development option will go a long way in bridging the gap between the rural and urban areas, thereby accelerating regional integration and development as a whole.